SERS active Ag–SiO2 nanoparticles obtained by laser ablation of silver in colloidal silica - Cristina Gellini; Francesco Muniz-Miranda; Alfonso Pedone; Maurizio Muniz-Miranda (Beilstein Journal of Nanotechnology, 2018)
Highly stable Ag–SiO2 nanoparticle composites were first obtained by laser ablation of a silver target in an aqueous colloidal dispersion of silica and examined by UV–vis absorption spectroscopy, transmission electron microscopy and Raman spectroscopy. The surface enhanced Raman scattering (SERS) activity of these nanocomposites was tested using 2,2’-bipyridine as a molecular reporter and excitation in the visible and near-IR spectral regions. The computational DFT approach provided evidence of ligand adsorption on positively charged adatoms of the silver nanostructured surface, in a very similar way to the metal/molecule interaction occurring in the corresponding Ag(I) coordination compound.